2011
DOI: 10.1016/j.virusres.2011.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Induction and evasion of type I interferon responses by influenza viruses

Abstract: Influenza A and B viruses are a major cause of respiratory disease in humans. In addition, influenza A viruses continuously re-emerge from animal reservoirs into humans causing human pandemics every 10–50 years of unpredictable severity. Among the first lines of defense against influenza virus infection, the type I interferon (IFN) response plays a major role. In the last 10 years, there have been major advances in understanding how cells recognize being infected by influenza viruses, leading to secretion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
189
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(202 citation statements)
references
References 100 publications
3
189
0
4
Order By: Relevance
“…Members of both the orthomyxovirus (47) and paramyxovirus (48,49) families employ different strategies to block the cellular antiviral response, including the suppression of host cell protein expression in infected cells (47,50). However, neither myxovirus family induces rapid host cell lysis or apoptosis, and genome transcription and replication of the Paramyxoviridae occur in the cytosol, while the orthomyxoviruses adhere to nuclear transcription and replication of their genetic information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of both the orthomyxovirus (47) and paramyxovirus (48,49) families employ different strategies to block the cellular antiviral response, including the suppression of host cell protein expression in infected cells (47,50). However, neither myxovirus family induces rapid host cell lysis or apoptosis, and genome transcription and replication of the Paramyxoviridae occur in the cytosol, while the orthomyxoviruses adhere to nuclear transcription and replication of their genetic information.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the influenza virus NS1 protein has been demonstrated to block correct processing of cellular mRNAs (47), while the MeV N protein has been implicated in interference with host mRNA translation through interaction with the translation initiation factor eIF3-p40 (63). Values represent averages and SD for three independent experiments; each sample was analyzed in duplicate.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of IFNAR1 is critical for efficient IAV replication. Since IFNAR1 is essential for triggering type I IFN-mediated antiviral responses (12)(13)(14), IFNAR1 degradation by IAV could be beneficial to virus replication. It was also reported that inhibition of ubiquitin-proteasome degradation pathway represses IAV infection and propagation (57).…”
Section: Iav Induces the Degradation Of Ifnar1 Proteinmentioning
confidence: 99%
“…Therefore, type I IFNs play an important role in the host defense system against viruses, including IAV (12)(13)(14). Influenza viral RNAs with a 5=ppp trigger the retinoic acid-inducible gene 1 (RIG-I)-mediated signaling pathway (15).…”
mentioning
confidence: 99%
“…When host cells are invaded by viruses, the cells immediately respond by synthesizing and secreting alpha and/or beta interferon (IFN-␣/␤) (IFN pathway), which subsequently binds to its cognate receptors on the cell surface (8,9). The engagement of IFN-␣/␤ and its receptors activates JAK1 and TYK2 to phosphorylate the STAT1 and STAT2 signal transducers (JAK-STAT pathway).…”
mentioning
confidence: 99%